Le nicodémisme dans l’œuvre de Juan de Valdés - Elvezio Canonica (Les Cahiers de Framespa)
The purpose of this paper is to return to the question of the nicodemism of Juan de Valdés, that Marcel Bataillon assumed in a 1973 article. Based on the reflection of the illustrious French Hispanist, we propose to nuance it, especially with regard to the Valdesian production of the Neapolitan period (1535-1541). After having described in broad outline the cultural and biographical context, we first attach ourselves to a "Nicodemite" reading of the Diálogo de doctrina cristiana (1529) and, secondly, to that of the works written in Naples which had first an oral diffusion, before being published after the death of its author, often in Italian translations. In these doctrinal works one appreciates not a return to the bosom of the Church, as Bataillon seemed to imply, but a reaffirmation, even a deepening, of the "nicodemism" of Juan de Valdes, whose principal disciples had to leave Italy and, for some of them, suffer the wrath of the Inquisition.